Effects of movement from a postural maintenance position on lumbar hemodynamic changes - Kumamoto, Tsuneo (J Phys Ther Sci, 2016)
[Purpose] To investigate the effects of movement from a postural maintenance position on lumbar hemodynamic changes, in order to prevent lower back pain and develop exercise therapy. [Subjects and Methods] Twenty-five healthy adults (mean age: 23.2 years) participated in the study. During flexion-extension exercise, the subjects moved their trunks gradually to a flexed position from an upright posture while sitting and standing, and then returned to and maintained an upright (re-upright) position. In the extension–flexion exercise, the subjects moved their trunks gradually from an upright posture to an extended position, and back while maintaining an upright (re-upright) position. Lumbar spinal muscle activity and hemodynamic changes were evaluated during both exercises. [Results] During the flexion and extension exercises, increased trunk-flexion angle caused increased muscle activity, decreased oxygenated hemoglobin in the multifidus muscle, and increased deoxygenated hemoglobin in the multifidus and lumbar erector spinae muscles. Moreover, the muscle activities were nearly the same in the re-upright and upright positions, and total hemoglobin also increased. [Conclusion] In both standing and sitting positions, holding the trunk in a flexed position causes ischemic hemodynamic changes in the multifidus muscle; however, the hyperemic response when returning the trunk to an extended position may improve circulation.